Study of Synergistic Effect of Silica Fume and Fly Ash Inclusion in High Performance Concrete - Ranjan, Manish; Kumar, Sanjay; Sinha, Sanjeev (Engineering, Technology & Applied Science Research, 2024)
The use of Supplementary Cementitious Materials (SCMs) in the construction industry to reduce the carbon footprint associated with cement manufacturing is increasing worldwide. This study examined the synergistic behavior of two SCMs, Fly Ash (FA) and Silica Fume (SF), in the production of High-Performance Concrete (HPC). Using various amounts of SF and FA to replace cement, several ternary mixes were created and their strength, microstructure, durability and fresh state properties were evaluated. A Rapid Chloride Permeability test (RCPT) was performed to determine the resistance of the mixture to chloride ion penetration. Microstructural analysis was carried out utilizing Scanning Electron Microscopy (SEM) images to study the morphological characteristics of the mixes. The results revealed that the combined use of SF and FA in HPC significantly increased its durability and compressive strength owing to the pozzolanic reaction and filler effect. Microstructural investigation exhibited improved particle packing, refined pore structure, and the creation of more Calcium Silicate Hydrate (CSH) phases. Thus, SF and FA, when used in conjugation, optimize HPC performance and promise to be a sustainable and viable solution for reducing cement requirements.